The Actualization of Characters and References in The Classic Arabic Literature Criticism - Yusuf Haikal (Arabic Literature Department, 2021)
This study aims to give an overview, review and actualize referral sources in the literary criticism of classical Arabic along with the figures from the source of the referral, which is expected to help and enrich the knowledge and insight for learners criticism in Arabic literature. The method used is descriptive qualitative and the study of literature. Through this method the data and studies taken from various sources of literature are then described and presented in the form of words based on the focus of the book which became the main reference. From the discussion, it could be concluded that the scientific and the development of criticism in Arabic Literature in the classical, more precisely between the eighth century to the twelfth century, is the golden period of development in the scientific criticism in Arabic literature. Moreover, the four centuries was also born to a wide variety of artwork and writing a review or even find a theory and new things related to literary criticism. There are at least four books is the source of the referral (mashdar) literary criticism of classical Arabic that can be actualized and utilized as well as made the object of research to the development of scientific criticism in Arabic literature at the present time. The fourth book is Thabaqāt Fuchūlus-Syu'arā’, al-muwāzanah, al-badi’, and dalā'ilul i'jāz. The fourth book, and its author, is also a testament to the greatness of the development of criticism in Arabic literature in the classic, and has represented a wide range of novelty born of the development of scientific criticism in Arabic literature.